Determinants of Small-Scale Farmers' Intention to Use Smartphones for Generating Agricultural Knowledge in Developing Countries: Evidence from Rural India - Dirk Landmann; Carl-Johan Lagerkvist; Verena Otter (The European Journal of Development Research, 2020)
Access to and usage of smartphones for agricultural purposes amongst small-scale farmers in rural areas of developing countries is still limited. Smartphones may provide an opportunity to develop farmers' capacities with specific applications offering fast access to continually updated and reliable information. This study develops a framework to investigate the cognitive and affective behavioural drivers of smallholder farmers intention to use a smartphone in a developing country context. For this, survey data was collected from 664 randomly selected small-scale farmers in Bihar State, India in 2016. The analysis included a partial least square estimation of the behavioural model. The results confirm positive influences on the intention to use a smartphone for agricultural purposes through subjective norms, attitude, self-control, as well as positive and negative anticipated emotions. There is no evidence that negative anticipated emotions related to failure outweighed other factors. These results extend the academic literature with new conceptual insights and provide application-oriented implications for stakeholders, such as NGOs, extension services and research institutes.
Keywords: 330; Smartphone; Agriculture; Small-scale farmers; Theory of planned behaviour (TPB); Structural equation modelling (SEM); Partial least squares (PLS); Developing countries; India